Comparison Between Blood Haematology of Egyptian Freshwater Food Fish and Ornamental Fish - Abdelhamid Mohamed Abdelhamid; Mohamed Moaaz Refaey; Hazem Ga'far Mohammed El-Sayed; Gehad Ahmed Mo'aty (Yayasan Ahmar Cendekia Indonesia, 2021)
The present study was carried out to compare between some freshwater food fish species and some other freshwater ornamental fish species commonly known in Egypt, concerning the haematological parameters, dressing percent, fillet (boneless meat) percentage, and chemical composition of the fish flesh on dry matter basis. Four food fish species (Nile tilapia, grass carp, catfish, and Tobara from Manzalah Fish Farm, Dakahlia governorate, General Authority For Developing Fish Wealth, Ministry of Agriculture, Cairo, Egypt) and two ornamental fish (Koi and Fan-tail (Goldfish), from local ornamental fish trade shops, Mansoura, Dakahlia governorate, Egypt) species all belonging to the freshwater fishes were sampled, three fishes from each. Body measurements of the individual fishes were recorded, blood samples were withdrawn, live body weight was recorded, fish were dressed (eviscerated) and filleted, the flesh were minced, dried, and sieved for chemical analysis. From the forgoing results, it could be concluded that the worthiness comparison among fish species for physical, biochemical and haematological parameters, and fish quality must be done between similar species, sex, size, physiological status, nutritional status, rearing system. These parameters are variable and influenced by genetically and environmental aspects.